Fertilizer recommendation for cauliflower production in the Bogura region of Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2020)
An experiment was conducted to detect fertilizer doses in cauliflower (Brassica oleracea var. botryitis, L. Family: Cruciferae) during rabi season of 2016-17. The location for the study was at the Multi location Testing (MLT) site, (medium highland under AEZ-03) Goneshpur of Shibganj upazilla under Bogura district. The experiment was laid out in randomized complete block design (RCBD) with eight dispersed replications. There were eight nutrient packages viz. T1 = 100% NPKSZnB (STB), T2 = T1+ 25% N, T3 = T1+ 25% NP, T4 = T1+ 25% NK, T5 = T1+ 25% PK, T6 = T1+ 25% NPK T7 = 75% of T1 and T8 = Control. The highest yield (42.11t ha-1) was obtained from the treatment T6 which was statistically similar with the rest treatments except T7 (35.89 t ha-1) and T8 (18.36 t ha-1). In case of gross margin, the highest value, (824607) was also obtained from the treatment T6 followed by T3, T1 and T4. The treatment T6 (T1+ 25% higher NPK), fertilizer management practices produced higher in terms of cauliflower yield, gross return, gross margin over the other treatments. Therefore, the result revealed that recommended fertilizer dose N138.25 P50 K143.75 s 4.5 Zn 3.22 B 0.51 Kg ha-1 was optimum for maximizing the yield as well as economically and environmentally viable for cauliflower cultivation in Bogura region.Asian Australas. J. Biosci. Biotechnol. 2020, 5 (1), 1-5